The Pfs230 N-terminal fragment, Pfs230D1+: expression and characterization of a potential malaria transmission-blocking vaccine candidate - Shwu-Maan Lee (Malaria Journal, 2019)
Abstract Background Control and elimination of malaria can be accelerated by transmission-blocking interventions such as vaccines. A surface antigen of Plasmodium falciparum gametocytes, Pfs230, is a leading vaccine target antigen, and has recently progressed to experimental clinical trials. To support vaccine product development, an N-terminal Pfs230 antigen was designed to increase yield, as well as to improve antigen quality, integrity, and homogeneity. Methods A scalable baculovirus expression system was used to express the Pfs230D1+ construct (aa 552–731), which was subsequently purified and analysed. Pfs230D1+ was designed to avoid glycosylation and protease digestion, thereby potentially increasing homogeneity and stability. The resulting Pfs230D1+ protein was compared to a previous iteration of the Pfs230 N-terminal domain, Pfs230C1 (aa 443–731), through physiochemical characterization and in vivo analysis. The induction of functional antibody responses was confirmed via the standard membrane feeding assay (SMFA). Results Pfs230D1+ was produced and purified to an overall yield of 23 mg/L culture supernatant, a twofold yield increase over Pfs230C1. The Pfs230D1+ protein migrated as a single band via SDS-PAGE and was detected by anti-Pfs230C1 monoclonal antibodies. Evaluation by SDS-PAGE, chromatography (size-exclusion and reversed phase) and capillary isoelectric focusing demonstrated the molecule had improved homogeneity in terms of size, conformation, and charge. Intact mass spectrometry confirmed its molecular weight and that it was free of glycosylation, a key difference to the prior Pfs230C1 protein. The correct formation of the two intramolecular disulfide bonds was initially inferred by binding of a conformation specific monoclonal antibody and directly confirmed by LC/MS and peptide mapping. When injected into mice the Pfs230D1+ protein elicited antibodies that demonstrated transmission-reducing activity, via SMFA, comparable to Pfs230C1. Conclusion By elimination of an O-glycosylation site, a potential N-glycosylation site, and two proteolytic cleavage sites, an improved N-terminal Pfs230 fragment was produced, termed D1+, which is non-glycosylated, homogeneous, and biologically active. An intact protein at higher yield than that previously observed for the Pfs230C1 fragment was achieved. The results indicate that Pfs230D1+ protein produced in the baculovirus expression system is an attractive antigen for transmission-blocking vaccine development.